Tocotrienol-Rich Tocomin Attenuates Oxidative Stress and Improves Endothelium-Dependent Relaxation in Aortae from Rats Fed a High-Fat Western Diet - Ali, Saher F.; Nguyen, Jason C. D.; Jenkins, Trisha A.; Woodman, Owen L. (Frontiers in Cardiovascular Medicine, 2016)
We have previously reported that tocomin, a mixture high in tocotrienol content and also containing tocopherol, acutely preserves endothelial function in the presence of oxidative stress. In this study we investigated whether tocomin treatment would preserve endothelial function in aortae isolated from rats fed a high fat diet known to cause oxidative stress. Wistar hooded rats were fed a western diet (WD, 21% fat) or control rat chow (SD, 6% fat) for 12 weeks. Tocomin (40 mg/kg/day sc) or its vehicle (peanut oil) was administered for the last 4 weeks of the feeding regime. Aortae from WD rats showed an impairment of endothelium-dependent relaxation that was associated with an increased expression of the NADPH oxidase Nox2 subunit and an increase in the vascular generation of superoxide measured using L-012 chemiluminescence. The increase in vascular oxidative stress was accompanied by a decrease in basal NO release and impairment of the contribution of NO to ACh-induced relaxation. The impaired relaxation is likely contributed to by a decreased expression of eNOS, calmodulin and phosphorylated Akt and an increase in caveolin-Tocotrienol rich tocomin, which prevented the diet-induced changes in vascular function, reduced vascular superoxide production and abolished the diet-induced changes in eNOS and other protein expression. Using selective inhibitors of nitric oxide synthase (NOS), soluble guanylate cyclase (sGC) and calcium activated potassium (KCa) channels we demonstrated that tocomin increased NO mediated relaxation, without affecting the contribution of endothelium-dependent hyperpolarization type relaxation to the endothelium-dependent relaxation. The beneficial actions of tocomin in this diet-induced model of obesity suggests that it may have potential to be used as a therapeutic agent to prevent vascular disease in obesity.